ANALISIS KOMPOSISI JENIS DAN POTENSI SIMPANAN KARBON PADA EKOSISTEM KARST DI RESORT TONDONG TALLASA TAMAN NASIONAL BANTIMURUNG BULUSARAUNG - Much Syachrir; St. Subaedah; Ayu K Parawansa (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
The purpose of this study is to identify the composition and potential of carbon deposits of karst ecosystem vegetation at the Tondong Tallasa Resort Management Division of Balocci Regional National Park I Bantimurung Bulusaraung National Park covering surface biomass (BAP). The research was conducted in April 2017 - June 2017 on the karst ecosystem in the flat area, the fault path, slope with a few stones, slopes with many rocks and hills in the Bantimurung Bulusaraung National Park. The dominant types consist of Syzygium acuminatissima and Dracontomelon dao in the flat primary forest, Kleinhovia hospital and Alstonia scholaris in the primary forest of broken paths, Pterocymbium tinctorium and Beilschmiedia gemmiflora in the primary forest slope of a few miles, Duabanga molucana and Garuga floribunda in primary forest slopes many stones, Duabanga molucana and Sterculia foetida in the primary forest of the dorsal hills. The results showed that the average mean carbon forest reserve was 56.26 ± 9.52 tons / ha, in the primary forest of fault paths was 44.64 ± 8.87 tons / ha, in the primary forests slope a slight rock of 52.12 ± 9.84 ton / ha, in primary forest slope of many stone of 15.39 ± 3.06 ton / ha, and in primary forest of hillside equal to 11.35 ± 2.26 ton / ha. Tree with diameter> 20 cm gives a significant contribution to total BAP ranging from 11.18 - 95.49 ton / ha or 43.63 - 84.86%. While trees with diameter of 5 - 20 cm only ranged from 6.73 - 15.55 tons / ha or 10.90 - 37.22%.